Influence of Hyperimmunserum anti-species serum to the kinetics of foot and mouth disease virus (FMPV) neutralisation - ΔΗΜΗΤΡΙΑΔΗΣ, Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
The influence on the kinetics of neutralisation of FMDV using hyperimmune rabbit serum —anti — guinea pig serum was studied.. The titre of hyperimmune rabbit serum — and — guinea pig serum used for immunodiffusion was 1:16. The titre of hyperimmune guinea pig antiserum to FMDV, type A22, was 1:50 in the completment fixation test (CFT) (100%) / and 1:512 in the serum neutralisation test Into the dilutions of hyperimmune guinea pig antiserum to FMDV type A22, it was added an equal volume of hyperimmune rabbit serum and — guinea pig serum (dilution 1:10 and 1:40) and the mixture was incubated for 60 at 37°C. Afterwards the titre of hyperimmune guinea pig antiserum to FMDV, type A22, was checked in this mixture by the CFT and the serum neutralization test using IBRS cells, it seems from the results of these assays that the hyperimmune rabbit serum anti — guinea pig serum does not affect the titre of the guinea pig hyperimmune serum in the CFT whereas in the serummeutralisation test this titre was increased fivefold. We think that this plhenomenon it might be of value in examing sera with low antibody titre.